Comparison of Lateral-flow Nanoparticle Fluorescence Assay and ELISA Method for Interferon-y Release Assay Test - Tandry Meriyanti; Maroloan Aruan; Diana Intan Lusiana Gabriella; Justina Andrea Renjaan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
The detection of latent tuberculosis (TB) infection to prevent progression to active TB disease is an essential part of the WHO's end-TB strategy. Diagnosis of latent TB infection is based on detecting immune responses to Mycobacterium tuberculosis antigens. Interferon Gamma Release Assays (IGRA) are superior to Tuberculin Skin Tests (TST) for detecting latent infection; however, the performance of IGRA is limited in resource-limited settings. This study evaluated the sensitivity, specificity, and agreement of the lateral-flow nanoparticle fluorescence assay (QIAreach QFT) compared with the ELISA method (QFT-Plus) as a reference test. This cross-sectional study was carried out in the laboratory department of Siloam Hospitals in Lippo Village, Banten, Indonesia, between January and June 2023. A total of 60 samples consisting of both males and females of all age groups were tested for QFT-Plus and were involved in the study using consecutive samples. Sensitivity, specificity, Negative Predictive Value (NPV), and Positive Predictive Value (PPV) of QIAreach QFT were 100% (95% CI 86.28-100), 70.96% (95% CI 51.96-85.78), 100%, (95% CI 84.56-100) and 73.53% (95% CI 55.64-87.12), respectively. The agreement calculation using Cohen's kappa coefficient, excluding indeterminate data, showed a kappa value 0.68 (95% CI 0.507-0.864). QIAreach QFT, with its superiority, could support the expansion of IGRA testing, particularly in remote areas, thereby helping the eradication attempt of TB infection.